Discrimination of Philippine coffee beans using an electronic nose system based on polymer-coated piezoelectric quartz crystal - Cabanilla, Sharlene R. (Transactions of the National Academy of Science and Technology, 2011)
Electronic nose (EN) generates and electrical signal in the presence of a substance causing aroma. In this study, the feasibility of a fabricated EN based on polymer-coated piezoelectric quartz crystals (PQC) was investigated for the discrimination of the different coffee varieties in the Philippines (i.e. Arabica, Robusta, Excelsa, and Liberica). The EN system that was employed was based on PQC coated with six sensing elements of different polarities [polyethylene glycol (PEG), polyvinylchloride (PVC), Silica (PVC/Silica), Cat-Ex (PVC/CatEx), polymethrylacrylate (PVC/PMAA), and Fluorosil (PVC/Flutor). Using the optimized conditions, coffee samples were sealed separately in the suitable vial and the headspace gas was pumped through the EN system using nitrogen gas. The gas phase detection was based on the corresponding change on the frequency of the crystal. Distinct radar plot quality profiles were obtained for each variety. Chemometric analysis of the responses from 48 different coffee samples using the EN was carried out using principal component analysis (PCA) and cluster analysis (CA). PCA and CA were applied to classify and to quantify how coffee samples are close to each other. The developed group of sensors was then able to categorize the different coffee varieties.